2005
DOI: 10.1159/000086187
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-2-Globin Gene Polyadenylation (AATAAA→AATAAG) Mutation in Hemoglobin H Disease among Kuwaitis

Abstract: Objectives: In the Arabian Gulf region, hemoglobin (Hb) H disease usually results from homozygosity or compound heterozygosity involving the α2-globin gene polyadenylation (poly A) signal (AATAAA→AATAAG) mutation (αTα). Here we document the clinical and hemato logical characteristics of children with Hb H disease being followed in Kuwait. Subjects and Methods: Twenty-four patients (0.5–12 years old, mean 4.7 ± 3.5 years) with persistent microcytic, hypochromic anemia (and normal iron stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The frequency of this mutation has been reported to be as high as 70.8 % in a study of 17 HbH patients from Kuweit [27]. Other studies conducted in Turkey reported its frequency as less than 10 % [7,[11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of this mutation has been reported to be as high as 70.8 % in a study of 17 HbH patients from Kuweit [27]. Other studies conducted in Turkey reported its frequency as less than 10 % [7,[11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mutation affecting the polyA signal of alpha2 gene is not specific to Saudi Arabian population. Three polyA signal mutations have been so far described: AATAAA to AATAAG was found specifically in Saudi Arabia and surrounding countries (Haider and Adekile, 2005), AATAAA to AATGAA was found in a Turkish population (Oner et al, 1997), and AATAAA to AATA was found in India and Western countries (Henderson et al, 2006;Prior et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The α 0 defects on the other hand, are either absent or seen only sporadically in most Arab countries and therefore Hb Bart's hydrops fetalis (homozygosity to an α 0 defect (− −/− −)) is almost absent (AlAllawi et al 2010b), while HbH (usually due to compound heterozygosity to and α 0 and α + ) is not common. Thus in many Arab countries, particularly in the Arabian Peninsula, the majority of cases of HbH disease are actually due to homozygosity to the common polyadenylation signal mutation (α polyA1 α/ α polyA1 α) (Adekile et al 1994;El-Kalla and Baysal 1998;Haider and Adekile 2005;Hellani et al 2009) The SCD in Arab countries Over the generations, the HbS gene has reached high frequencies in regions with past or present history of malaria endemicity due to the selective advantage of carriers to falciparum malaria. However, population migration has played a major role in distributing HbS gene even to malaria non-endemic regions.…”
Section: The Spectrum Of α-Thalassemia Mutations In Arab Countriesmentioning
confidence: 99%
“…This distribution is probably best explained by the supposed origin of the sickle cell mutation, with the Arab-Indian mutation originating in the Indus valley on the Indian subcontinent and subsequently spreading to Iran and Eastern Arabian Peninsula through trade routes and historical interactions (Daar et al 2000;Rahgozar et al 2000). The Benin haplotype on the other hand, has originated in Central West Africa and then spread vertically via population movement by trans-Saharan migration to North Africa and thence across the Mediterranean Sea to Bahrain Among 97 α-thalassemia chromosomes, the most common was the (α poly A1 α) (53 %), followed by (− α )and 4.2 % were undetermined (Haider and Adekile 2005) Of the 30 chromosomes from 15 patients with HbH disease, 86.7 % carried the (α polyA1 α), 10 % had (−α 3.7…”
Section: The Spectrum Of α-Thalassemia Mutations In Arab Countriesmentioning
confidence: 99%